2017
DOI: 10.1016/j.joca.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

A novel Wnt pathway inhibitor, SM04690, for the treatment of moderate to severe osteoarthritis of the knee: results of a 24-week, randomized, controlled, phase 1 study

Abstract: NCT02095548.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 21 publications
0
77
1
1
Order By: Relevance
“…These results implicate WNT5A and 5B as potential targets of disease-modifying drugs [16][17][18]. Based on the observation of residual MSC failure in OA joints, Wnt inhibitors have recently completed phase I clinical trials as first-in-class drugs [17]. Although these results suggest the efficacy of Wnt inhibitors as DMOADs, WNT ligands and pathways with different effects have not been separately assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results implicate WNT5A and 5B as potential targets of disease-modifying drugs [16][17][18]. Based on the observation of residual MSC failure in OA joints, Wnt inhibitors have recently completed phase I clinical trials as first-in-class drugs [17]. Although these results suggest the efficacy of Wnt inhibitors as DMOADs, WNT ligands and pathways with different effects have not been separately assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling disorder plays a critical role in stem cell failures, for example, hematopoietic stem cell senescence [14] and intestinal stem cell failure [15]. Based on this, regulators of Wnt signaling have been suggested as promising diseasemodifying osteoarthritis drugs (DMOADs) [12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…These preclinical data have been used to support the use of lorecivivint for the treatment of knee osteoarthritis in human clinical trials. Based on a phase 1 study with an excellent safety profile [45], phase II trials have recently been finished suggesting effectiveness on both signs and symptoms as well as structural damage in patients with knee osteoarthritis, in particular those without widespread pain [46,47]. As a caveat, data are currently only available in meeting abstract format.…”
Section: Lorecivivint Is a Small Molecule Wnt Pathway Inhibitormentioning
confidence: 99%
“…Completion of phase I clinical trials have demonstrated tolerability in humans with SM04960 undetected in plasma following intra-articular injection. Phase II trial assessment is required to support suggestions of improvement in OA pain and joint function 46 .…”
Section: Signalling Mechanisms Involved In Cartilage Homeostasismentioning
confidence: 99%